Harmoni Bahasa dalam Lagu 'Raiso Dadi Siji': Alih Kode dan Campur Kode Perwujudan Pendidikan Multibahasa - Agus Tri Wardana, Agoes Hendriyanto; Astuti , Sofia Rahma Dwi (Jurnal Penelitian Pendidikan, 2023)
Qualitative descriptive research by collecting data on the lyrics of the song "Raiso Dadi Siji". This song tells the story of a man who is married and has a wife, but still loves his affair very much. Data was collected through listening approaches and note-taking techniques involving song lyric text and performance videos of songs sung by Kevin Ihza and Niken Salindri. The study will be conducted in May 2023. The results of the study are as follows: in the lyrics of this song, there are two code-switching events that occur due to the influence of Javanese, as well as two code-mixing events that insert words in Javanese into the song lyrics. Kevin Ihza, in his lyrical section, contains nine elements that reflect code mixing and five elements that indicate code switching. Code switching is a phenomenon in which a person switches from the use of one language to another in communication, often occurring between different language clauses or phrases. Understanding and analyzing code mixing and code switching, we can sense the diversity of languages and cultures around us and use them to develop more inclusive approaches in communication and education.